1992
DOI: 10.5144/0256-4947.1992.140
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus in Saudi Arabia: The Clinical Pattern and Complications in 1,000 Patients

Abstract: A retrospective and prospective study of 1,000 ambulatory and hospitalized diabetic patients was done in Riyadh, Saudi Arabia. Saudis comprised 777 (77.7%) and non-Saudis 223 (22.3%). Sex distribution was equal among Saudis, males 389 (50.1%) and females 388 (49.9%), but non-Saudi males were predominant at 153 (68.6%), nonSaudi females 70 (31.4%) reflecting the preponderant male expatriate labor force. A proportion of different types of diabetes was: IDDM115 (11.7%), non-obese non-insulin dependent diabetes me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
4

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 17 publications
3
30
4
Order By: Relevance
“…[10][11][12][13][14][15][16][17] The prevalence of proteinuria is higher in this study than that reported by Fatani et al 18 and Famuyiwa et al 19 and this is because both investigators studied diabetic nephropathy as part of a global evaluation of all complications of diabetes. Fatani et al used dipstick positivity as their definition of diabetic nephropathy, which could be affected by the concentration of urine since diluted urine may test negative.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…[10][11][12][13][14][15][16][17] The prevalence of proteinuria is higher in this study than that reported by Fatani et al 18 and Famuyiwa et al 19 and this is because both investigators studied diabetic nephropathy as part of a global evaluation of all complications of diabetes. Fatani et al used dipstick positivity as their definition of diabetic nephropathy, which could be affected by the concentration of urine since diluted urine may test negative.…”
Section: Discussioncontrasting
confidence: 55%
“…This is similar to what has been observed in several cross-sectional studies. 11,19,30 Other studies, the majority of them in IDDM patients, have shown that the control of systemic blood pressure and, in particular, the reduction in the intraglomerular pressure is the major factor for preventing and halting the rate of decline in glomerular filtration rate in addition to reduction of albuminuria. 31 -35 We did not find a good correlation between degree of proteinuria and diabetic control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] Compared to complications in the peripheral nervous system, long-term diabetic complications in the central nervous system are relatively subtle and occur more frequently than is believed. Diabetes literature is replete with information on the vascular complications of neuropathy, nephropathy, retinopathy, coronary artery disease and peripheral vascular disease, but little information is available on the cerebrovascular disease in diabetic patients.…”
mentioning
confidence: 99%
“…A recent study of 1000 patients with DM cared for at our institution showed only 40% to be on insulin treatment. 19 In addition, inpatient ophthalmological services are rendered to our diabetic population at another facility, hence contributing to a lower occupancy rate. Table 4 shows a comparison of our results with those two studies that are similar in design to ours and reported from Tanzania 6 and Denmark, 5 representing developing and developed nations respectively.…”
Section: Discussionmentioning
confidence: 99%